Characteristics of Sago in the Maluku Islands (Taxonomy, Morphology, Species, and Productivity) - Riry, Roberth Berthy (Universitas Pattimura, 2022)
Sago is a very potential plant in the Maluku Islands, is a natural wealth that is bestowed by God for some Maluku people and has played an essential role for the community since ancient times, both as a staple and additional food as well as its function as a building material and its role in environmental sustainability, especially water management control. The area of sago land in the Maluku Islands is currently 58,185 ha; it is likely to be even broader if a detailed inventory process is carried out. With this area, the potential for sago starch in Maluku reaches 465,180 tons/year, and only 46,000 tons/year has been utilized, or about 10%, which means that 90% of sago starch is lost in the forest yearly. On the other hand, public attention to sago is decreasing or even disappearing, especially in urban communities. Urban communities generally eat less